IMAGE FORMING APPARATUS - ISHIZUKA, Yusuke; KOGURE, Seiichi; AKIYAMA, Takuya; HATTA, Hirotaka; GOTO, Yutaka; KIMURA, Hideki; KIKUCHI, Hiroshi; AOKI, Yuuki (2024)
An image forming apparatus includes a toner image bearer, a transfer device, a cleaner, a bias power source, and circuitry. The toner image bearer bears a toner image. The transfer device performs a transfer process The cleaner contacts the toner image bearer to remove transfer residual toner that is subject to the transfer process and remove untransferred toner that is not subject to the transfer process. The bias power source applies one of a first bias and a second bias different from the first bias to the cleaner. The circuitry controls the bias power source to output the first bias to the cleaner in response to a start of an image forming operation to remove the untransferred toner from the toner image bearer and control the bias power source to switch an output from the first bias to the second bias.